DOMESTIC VIOLENCE AMONG PREGNANT WOMEN - Habib, Sadia; Abbasi, Nasreen; Khan, Bushra; Danish, Nargis; Nazir, Quratulain (Journal of Ayub Medical College Abbottabad, 2018)
ABSTRACT: BACKGROUND: Physical and verbal abuse of women during pregnancy is now widely recognized as an important public health problem. In Muslim societies and especially underdeveloped countries, domestic violence is often under reported. Research is needed to highlight factors which place the women at risk of abuse. METHODS: This is a cross sectional study conducted at Ayub Teaching Hospital & Benazir Bhutto Shaheed Teaching Hospital, Abbottabad (from January 2015 to December 2016). Pregnant women were inquired regarding history of abuse by husband and sociodemographic characteristics was noted in a Performa to analyse the risk factors for domestic violence. RESULTS: The overall prevalence of any form of domestic violence was 35%. Out of 1000 pregnant women, 270 (27%) suffered from simple violence, 50(5%) were victims of graviousassault and only 15(1.5%)gave history of fatal assault. Urban residence, older age, lower education and lower income are more often associated with occurrence of domestic violence. CONCLUSION: Domestic violence during pregnancy is a common & often neglected psychosocial health problem. High risk population needs to be identified so that preventive strategies can be planned & implemented. Background: Domestic violence during pregnancy is an important social & health issue in all societies. In Muslim world and particularly underdeveloped countries, domestic violence is often under reported. It is the need of hour to encourage reporting of such events & implementation of research-based policies for prevention of women abuse & support of the victims of domestic violence (DV). The objective of this study was to highlight this neglected social problem of our society & to identify at risk population. Methods: This is a cross sectional study conducted at Ayub Teaching Hospital & Benazir Bhutto Shaheed Teaching Hospital, Abbottabad (January 2014 to December. 2016). Pregnant women were inquired regarding history of abuse by husband and sociodemographic characteristics were noted in a Performa to analyse the risk factors for domestic violence. Results: The overall prevalence was found to be 35%. Out of 1000 pregnant women, 270 (27%) suffered from simple violence and 60 (6%) were victims of grievous assault. Violence among pregnant women is found to be more prevalent among residents of urban areas, women of older age being uneducated & belonging to poor socioeconomic status. Conclusion: Domestic violence during pregnancy is a common & often neglected psychosocial health problem. High risk population needs to be identified so that preventive strategies can be planned & implemented. Keywords: Domestic violence; Partner abuse; Pregnancy; Pregnant women